Optimizing Healthcare Services Through Social Capital: An Analysis of Community Health Centers in Cilacap Regency - Imam Santosa; Joko Santosa; Rully Gianfin Arrakhman; Anggita Chairiah (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2026)
The role of social capital, trust, cooperation, and community networks has received limited empirical attention in explaining why certain community health centers (Puskesmas) can maintain effective service delivery despite structural limitations. This study aims to examine how social capital contributes to the optimization of healthcare services at Puskesmas Sampang and Kroya in Cilacap Regency and to explore how community networks, solidarity, and trust mitigate the challenges posed by digital and infrastructural constraints. Methods: A qualitative case study design was employed, drawing on in-depth interviews, participant observation, focus group discussions, and supporting documents. Data were analyzed using an interactive model through coding, categorization, and thematic interpretation. The findings reveal that strong social networks, particularly family ties, neighborhood associations, religious groups, and community WhatsApp networks, serve as critical channels for the exchange of health information and facilitate patient navigation of digital systems. Mutual trust between patients and healthcare workers reinforces institutional legitimacy, while community solidarity helps compensate for limited digital literacy, especially among elderly and low-income patients. However, challenges persist, including inconsistent digital system use, administrative bottlenecks, and occasional misuse of social ties that affect fairness in queue management. Digital innovation improves efficiency but reduces interpersonal interaction among staff. Social capital plays a pivotal role in sustaining rural healthcare performance by enhancing access, trust, and community participation. While it strengthens institutional resilience, it cannot fully substitute for structural improvements. Integrating community-based networks with inclusive digital literacy initiatives is essential to achieving equitable and optimized healthcare services in rural settings.